(untitled) (Applied Biological Research, 2023)
Two nematode trapping fungi were isolated from the arable soil samples collected from district Anand (Gujarat) India and identified on the basis of their culture-morphological characteristics and 18S rRNA gene sequencing as Arthrobotrys conoides (GenBank accession No. JX979095) and Duddingtoniaflagrans (GenBank accession No. JX979094). These fungal isolates were assessed for their trapping efficiency against root knot diseascausing nematode Meloidogyne spp., isolated from the infected tomato plants. When incubated with nematodes for 24 hr, the trapping efficiency of A. conoides and D. flagrans was 92-95 and 22- 29%, respectively. Growth conditions with respect to medium, temperature and pH were also optimized. This study showed that A. conoides is a promising candidate to control root-knot nematodes. Phylogenetic relationship with other nematophagous fungi showed that isolates formed monophyletic clade with other nematode trapping fungi as well.